Hidden surface channel in two-dimensional multilayers. (1st July 2022) - Seo, Youkyung; Kim, Soo Yeon; Kim, Yeeun; Kim, Chulmin; Lee, Byung Chul; Park, Yoon Hee; Chae, Minji; Hong, Youjin; Seong, Min Kyung; Ko, Changhyun; Cresti, Alessandro; Theodorou, Christoforos; et al.
Abstract: Numerous carrier scatterers, such as atomic defects, fixed oxide charges, impurities, chemical residues, and undesired surface adsorbates, including oxygen and water molecules, strongly degrade the carrier mobility of atomically thin two-dimensional (2D) materials. However, the effect of surface adsorbates and surface oxidation on the carrier density profile along the thickness of 2D multilayers is not well known, particularly for a substantial interruption in the formation of the top-surface channel. Here, we uncover a hidden surface channel in p-type black phosphorus and n-type rhenium disulfide multilayers originating from undesired ambient adsorbates and surface oxides that not only populate hole density (or reduce electron density) but also suppress carrier mobility. The absence of a second peak in the transconductance curve under ambient conditions indicates the disappearance of the top-surface channel inside the 2D multilayers, which is a possible indicator for the cleanliness of the top surface and can be used in gas sensor applications. Moreover, the negligible variation in the drain bias polarity-dependent turn-on voltage for the bottom channel under ambient conditions validates the exclusive contribution of surface adsorbates to the formation of the top channel in 2D multilayers. Our results provide a novel insight into the distinct carrier transport in 2D optoelectronic devices and diverse sensors.